2008
DOI: 10.3858/emm.2008.40.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xanthohumol on melanogenesis in B16 melanoma cells

Abstract: Xanthohumol (XH), the principal prenylflavonoid of the hop plant (Humulus lupulus L.), dose-dependently inhibited isobutylmethylxanthine (IBMX)-induced melanogenesis in B16 melanoma cells, with little cytotoxicity at the effective concentrations. Decreased melanin content was accompanied by reduced tyrosinase enzyme activity, protein and mRNA expression. The levels of tyrosinase-related protein 1 and 2 mRNAs were decreased by XH. XH also inhibited α-melanocyte stimulating hormone-or forskolin-induced increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
2
34
0
1
Order By: Relevance
“…CEFV was found to inhibit mRNA and protein levels of MITF in a dose-dependent manner, MITF is known as a major transcription factor in the regulation of tyrosinase expression, and thus plays a critical role in melanin biosynthesis. [8][9][10][11] Our results are consistent with the findings of a recent report 37) that xanthohumol (XH) significantly decreased mRNA and protein levels of MITF, suggesting that XH inhibits MITF transcription.…”
Section: Discussionsupporting
confidence: 82%
“…CEFV was found to inhibit mRNA and protein levels of MITF in a dose-dependent manner, MITF is known as a major transcription factor in the regulation of tyrosinase expression, and thus plays a critical role in melanin biosynthesis. [8][9][10][11] Our results are consistent with the findings of a recent report 37) that xanthohumol (XH) significantly decreased mRNA and protein levels of MITF, suggesting that XH inhibits MITF transcription.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, aleosin, licorice extract, ascorbic acid and soy proteins have been used to interrupt the process of melanogenesis [6]. We also recently reported that xanthohumol, scoparone and Angelica gigas extract exerted a potent inhibitory effect against melanogenesis in B16 melanoma cells [9][10][11]. During screening for new skin-whitening agents from natural sources, we found that the saponification product of evening primrose oil (sap-EPO) effectively whitened skin that had been subjected to UV-induced hyperpigmentation.…”
Section: Introductionmentioning
confidence: 97%
“…23) In addition, xanthohumol, a principal prenylflavonoid, has been reported to have antimelanogenesis effects by acting on cAMP-dependent signal transduction in melanocytes. 24) Since 1-3 have structures that are similar to these compounds, it is possible that their mechanisms of action against melanin biosynthesis are the same. Further biological activities of 1-3 are now being investigated.…”
mentioning
confidence: 99%